1995
DOI: 10.3181/00379727-209-43886a
|View full text |Cite
|
Sign up to set email alerts
|

Control of Collagen Deposition in Mammalian Lung

Abstract: This review considers the mechanisms controlling collagen deposition in mammalian lung in five different states: normal development, fibrosis, erosion, pneumonectomy, and the steady state. Deposition is the net result of positive and negative processes. The major positive processes are control of cell number and type, regulation of transcription and translation, post-translational modifications, fibril formation, and covalent cross-linking. The negative mechanisms are intracellular degradation, collagenase-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 126 publications
0
49
0
2
Order By: Relevance
“…Two recent findings may provide exciting future avenues for regulation of TGF-11 activity and therefore, lung fibrosis. Thrombospondin was found to be a major activator of TGF-,B1 by binding to and inducing a conformational change in the latency-associated peptide of TGF-P (148); and the integrin av16, which is upregulated on epithelial cells in response to lung inflammation, induces spatial activation ofTGF-,B1 (149 TGF-PI has numerous biologic activities including immunomodulatory (158), both pro-and antimitogenic (159,160), and profibrotic through increases in extracellular matrix synthesis and inhibition of matrix degradation (161). TGF-W_ inhibits proliferation of epithelial cells and thus could potentially extend the fibroproliferative phase following lung injury, since reepithelialization is purported to limit the formation of granulation tissue (162).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent findings may provide exciting future avenues for regulation of TGF-11 activity and therefore, lung fibrosis. Thrombospondin was found to be a major activator of TGF-,B1 by binding to and inducing a conformational change in the latency-associated peptide of TGF-P (148); and the integrin av16, which is upregulated on epithelial cells in response to lung inflammation, induces spatial activation ofTGF-,B1 (149 TGF-PI has numerous biologic activities including immunomodulatory (158), both pro-and antimitogenic (159,160), and profibrotic through increases in extracellular matrix synthesis and inhibition of matrix degradation (161). TGF-W_ inhibits proliferation of epithelial cells and thus could potentially extend the fibroproliferative phase following lung injury, since reepithelialization is purported to limit the formation of granulation tissue (162).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…TGF-31 has been shown to influence collagen accumulation at many of the key stages in collagen metabolism and degradation, beginning with induction of procollagen gene transcription (161,165). A transgenic mouse containing a rat type 1 alpha-1 collagen promoter fused to the chloramphenicol acetyltransferase (CAT) reporter gene has been studied in dermal wound and bleomycin lung injury models, and revealed that subcutaneous injection of TGF-W1 increases the CAT transgene expression but only in a subpopulation of dermal fibroblasts, even though alpha-1 collagen was expressed throughout the dermis (166 Collagen synthesis and degradation is an ongoing process in the lung, and TGF-,B1 has been shown to reduce the proportion of procollagen that is degraded within lung fibroblasts prior to secretion (167).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Once monocytes reach the area of inflammation, they become activated and begin phagocytizing bacteria and damaged cells, including neutrophils and fibrin deposits and tissues. Collagenases and elastases are released from the macrophages that destroy connective tissue [22]. A plasminogen activator is released, resulting in the production of plasmin and the tissue matrix relaxes [73].…”
Section: Cells Of Chronic Inflammationmentioning
confidence: 99%